Effect of Early Marriage on Reproductive and Sexual Health - Eros Rosmiati; Syamsulhuda Budi Mustofa; M. Zen Rahfiludin (Budapest International Research and Critics University, 2022)
Early marriage, defined as formal or informal marriage before the age of 18, occurs widely throughout the world. Early marriage has a direct impact on girls' education, sexual and reproductive health, and psychological well-being. In this regard, the current review is conducted to examine the sexual and reproductive health consequences of child marriage. This research uses library research methods or literature research. Literature research is a systematic activity that involves various stages of collecting, processing, and summarizing data using certain methods to find solutions to problems. Early marriage as a result of poverty has many adverse consequences on girls' sexual and reproductive health including death in childbirth, physical and sexual violence, isolation, depression, cervical cancer and risk of sexually transmitted diseases (STDs). Teenage pregnant women have a higher risk of premature birth and more neonatal death than other women. Marriage of girls at an early age can increase the risk of sexual and reproductive complications. Therefore, training programs should be implemented to raise awareness of the community, parents, and religious leaders, to empower girls in this regard.